2011
DOI: 10.1021/la203253m
|View full text |Cite
|
Sign up to set email alerts
|

Single-Layered Graphene Oxide Nanosheet/Polyaniline Hybrids Fabricated Through Direct Molecular Exfoliation

Abstract: In this study, we used direct molecular exfoliation for the rapid, facile, large-scale fabrication of single-layered graphene oxide nanosheets (GOSs). Using macromolecular polyaniline (PANI) as a layered space enlarger, we readily and rapidly synthesized individual GOSs at room temperature through the in situ polymerization of aniline on the 2D GOS platform. The chemically modified GOS platelets formed unique 2D-layered GOS/PANI hybrids, with the PANI nanorods embedded between the GO interlayers and extended o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…Variation in the XRD spectrum is also observed for PDA composites prepared under different temperature conditions because of the influence of experimental conditions on the exfoliation rate of RGO fillers [28]. The peak centered at 26° corresponding to the (002) plane of graphite [29] is observed in Fig. 2b [30].…”
Section: Characterization Of Polymer Nanocompositesmentioning
confidence: 90%
“…Variation in the XRD spectrum is also observed for PDA composites prepared under different temperature conditions because of the influence of experimental conditions on the exfoliation rate of RGO fillers [28]. The peak centered at 26° corresponding to the (002) plane of graphite [29] is observed in Fig. 2b [30].…”
Section: Characterization Of Polymer Nanocompositesmentioning
confidence: 90%
“…First graphite was converted into graphite oxide using modified Hummer's method reported by Chen et al [10]. In the second step, the graphite oxide was chemically reduced using hydrazine to reduced graphene oxide [11].…”
Section: Synthesis Of Reduced Graphene Oxide-silicamentioning
confidence: 99%
“…The synthesized GO was then subjected to disperse in either aqueous or organic solvents. Functionalization of polymer with GO/rGO occur (a) monomer, initiator and GO mixed together and follow in situ polymerization to get graphene-based polymer composites [49][50][51]; (b) this method comprises the synthesis of polymer followed by mixing with GO/rGO to get the desired product [52].…”
Section: Chemical Polymerizationmentioning
confidence: 99%
“…Vallés et al reported the simultaneous reduction GO and PANi followed by the method reported by Jiménez et al [53] It includes in situ oxidative polymerization of aniline in presence of dispersed GO [49]. However, Chen et al synthesized PANi nanorod embedded single layer GO nanosheets by in situ polymerization method, where molar ratio of aniline to APS was fixed at 1:1; the weight ratio of GO to aniline was 1:2 [50]. Recently, Yang et al reported that sulfonated PANi-GO nanocomposite and poly(m-aminobenzenesulfonic acid)-GO hybrid material by mixing all the required component to get the desired product [51].…”
Section: Chemical Polymerizationmentioning
confidence: 99%